2022
DOI: 10.1001/jamaoto.2021.3673
|View full text |Cite
|
Sign up to set email alerts
|

Falls Among People With Bilateral Vestibulopathy

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
11
1
Order By: Relevance
“…42,51,52,54 The percentage of participants with BVP with a recent history of falls (48%) was slightly higher than the literature average of 42% reported in a previous review on falls in BVP. 4 We observed a significant association between age and Mini-BESTest total score in both BVP and healthy groups. One of the included studies with healthy control data has previously reported an age-balance relationship.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…42,51,52,54 The percentage of participants with BVP with a recent history of falls (48%) was slightly higher than the literature average of 42% reported in a previous review on falls in BVP. 4 We observed a significant association between age and Mini-BESTest total score in both BVP and healthy groups. One of the included studies with healthy control data has previously reported an age-balance relationship.…”
Section: Discussionmentioning
confidence: 57%
“…About 30-40% of people with BVP suffer from oscillopsia (movement induced blurred vision) during head motion, due to reduced or absent vestibular-ocular reflex (VOR) . 3 In addition, people with BVP have a higher risk of falls, 4 as well as increased variability in various gait parameters 5,6 and often report difficulty and instability while walking in dimly lit environments and on uneven ground. [7][8][9] Due partly to these symptoms, avoidance of falls and reduction in mobility may occur and negatively impact societal participation, which may in turn be linked with the increase in depression and reduced quality of life in people with vestibular disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, approximately 5% of patients with MD experience syncope during drop attacks, 37 which may increase their risk of fall‐related injuries. Furthermore, patients with bilateral MD or delayed contralateral MD may exhibit an even higher risk of falling than that of patients with other forms of MD 40–43 . By contrast, studies have yielded contradictory results regarding vestibular vertigo as a cause of traffic accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Human motion measurement and analysis represent a major topic in the medical field to understand people's gross motor function, e.g. to identify possible risks of fall 1 or to understand gait deviations 2 . This is usually performed with an optoelectronic system in a gait laboratory.…”
Section: Background and Summarymentioning
confidence: 99%